Ochratoxin A and microbiological contamination of craft beers made in Cuenca, Ecuador - Michelle Castro-Arteaga; Katty Cabezas-Terán; Jorge Saquicela; Silvana Donoso-Moscoso; Johana Ortiz-Ulloa (Agroindustrial Science)
Craft beers are usually produced on a small scale following atypical recipes and processes to achieve flavor innovation. Beers’ hop composition offers a natural protection against biological contamination. Nevertheless, mycotoxins, such as ochratoxin A, can persist through the brewing process into the final product. In this study, the microbiological quality (aerobic mesophilic bacteria, mold, and yeast) via plate counts and ochratoxin A occurrence by HPLC-FLD were assessed in 42 samples of craft beer brewed in Cuenca, Ecuador. Aerobic mesophilic bacteria were present in 92.8% of analyzed samples and ranged from 6.6 to 8.4 log CFU mL-1. Mold and yeast were present in 95.2% of craft beers, ranging between 6.6 and 8.2 log CFU mL-1. Ochratoxin A was detected in 24% of craft beer samples, from which Ale type beers showed the highest contamination (0.03-0.51 ng mL-1). None of the craft beer samples presented levels of ochratoxin A contamination above the permitted limit; while in most of the samples, microbiological contamination exceeded the reference limits applied for industrial beer. Although craft beer production does not follow a standardized process, to ensure the safety of this popular alcoholic beverage, minimum requirements for microbiological and chemical contaminants must be considered as well as further research into control and mitigation strategies throughout brewing.